Ultrafast actuation of Ni-Mn-Ga micropillars by pulsed magnetic field. (15th March 2019) - Musiienko, Denys; Saren, Andrey; Straka, Ladislav; Vronka, Marek; Kopeček, Jaromír; Heczko, Oleg; Sozinov, Alexei; Ullakko, Kari
Abstract: We report on the pulsed magnetic field actuation of single crystalline Ni-Mn-Ga cuboid micropillars with dimensions of 40 × 45 × 120 μm 3, created by focused ion beam milling followed by electrochemical etching. Based on the experimental and modelled results, we differentiate between type I and type II twin boundary motion in the micropillar, which display about an order difference in actuation velocities. Magnetically-induced reorientation of a micropillar was obtained in less than 5 μs by type II twin boundary motion. Our results suggest the possibility of fabrication of magnetic shape memory microdevices with working frequencies up to 100 kHz. Graphical Abstract: